Study of effect of anthelmintic treatment on metabolic profile of anestrus Haryana cows - SINGH, C P; SAXENA, ATUL (The Indian Journal of Animal Reproduction, 2023)
Thirty four Haryana cows were selected (24-anestrus and IO-normal cyclic) from the university farm for the study ofmetabolic profile of anestrus cows in response to anthelmintic treatment. Faecal samples of these animals were examined forthe presence of parasitic eggs. Haematobiochemical studies viz. haemoglobin (Hb ), glucose and total protein were alsoconducted. An overall increase ofHb, serum glucose and total protein concentration in anthelmintic treated animals was greaterthan untreated group. This might be because of increased feed consumption by anthelmintic treated animals. The concentrationof Hb was significantly higher (P
Keywords: Anthelmintic; metabolic profile; Hb; glucose; total protein; infertility; cow